Don Camillo e i penitenti d'oggi - Quartieri, Fabio (Rassegna di teologia, 2025)
The paper sketches the image of the Sacrament of Penance that emerges from the famous tales by G. Guareschi which have Don Camillo as the protagonist. The detailed reconstruction of this image is functional in comparison with the imaginary still widespread among believers and non-believers (often not too different from what was narrated more than sixty years ago) and with the current practice of the sacrament, which perhaps struggles to renew itself also due to the ballast created precisely by this widespread imagery.